Problems associated with alcohol consumption by university students - Guillermo Alonso Castaño-Perez; Gustavo Adolfo Calderon-Vallejo (Universidade de São Paulo, 2014)
OBJECTIVES: the aim of this study was to analyze alcohol consumption by university students and psychosocial problems related.METHOD: descriptive correlational study that included 396 university students. The "Alcohol Use Disorders Identification Test" - (AUDIT) - and an "ad hoc" questionnaire were used as instruments to assess the associated problems.RESULTS: of the total sample, 88.6% drank, 20.5% had harmful consumption and 14.9% were at risk of dependence according to AUDIT. The study showed important results related to harmful alcohol consumption and dependence, with damage to the academic performance, social relationships, psychological status and sexual condition.CONCLUSIONS: complications caused by problematic alcohol consumption by university students, which is high in this group due to the high prevalence of their alcohol consumption, highlights the importance of promoting programs to prevent the abuse and dependence of this substance in universities.